Rehumanizing the graduate seminar by embracing ambiguity: The Athena Co-Learning Collective. Issue 4 (3rd April 2021) - Rice, Jennifer L.; Trauger, Amy; Allums, Coleman; Berry, Rachelle; Biesel, Shelly; Bivens, Briana; Black, Sara; Crespo, Christina; Kemmerlin, Aspen; Wesnofske, Chelsea; Co-Learning Collective, The Athena
Abstract: This Viewpoint introduces the Athena Co-Learning Collective: A group of faculty and graduate students at the University of Georgia committed to teaching and learning differently in the academy. In particular, we describe the Athena Co-Learning Collective's efforts to reject masculine forms of teaching and learning that are characteristic of the traditional seminar. Instead, we focus on rehumanization, as offered by Katherine McKittrick, to render visible a wider range of viewpoints and experiences, as well as ambiguity, as described by Gloria Anzaldúa, to embrace the discomfort and ambiguity that is part of valuing multiple stories. We then describe our practices of co-learning and collective writing used to achieve these goals, focusing on both our successes and failures. We conclude with provocations for generating collectivity in our graduate seminars and changing the stakes of graduate teaching to allow for more transformative learning.